THE VALUES OF ISLAMIC LAW IN JAVA TONDANO COMMUNITY DIVERSITY IN THE MIDDLE OF MINAHASA CHRISTIAN MAYORITY IN THE CONTEXT OF BHINNEKA (DIVERSITY) - Fauzul Aliwarman (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
The Javanese Tondano (Jaton) community is a different entity (with Muslim beliefs) compared to other Minahasa communities. This is formed from a piece of past history that brought them to the land of Minahasa. In an effort to maintain their identity there is a power relationship that is formed between the Minahasa Christians and the Jaton people. This study aims to see the application of Islamic law values in the diversity of the Jaton Society in Minahasa and the challenges of Javanese Tondano Muslim diversity in the perspective of diversity. The method used is through an empirical juridical approach with qualitative descriptive analysis. The results obtained indicate the value of the Jaton community's diversity as an ethnic identity with a very strong belief in holding Islamic law in interacting with local communities. Even though the early and later generations had mixed marriages with Minahasan people themselves and other ethnic groups, they still maintained their beauty and Javanese culture until now. They did not choose to become reformist Islam which has recently flourished in Indonesia. However, their existence is not considered to disturb or threaten the existence of the majority of Christian Minahasa people.